2022
DOI: 10.1021/acsapm.1c01353
|View full text |Cite
|
Sign up to set email alerts
|

Robust, Reusable, and Antioxidative Supramolecular Adhesive to Inorganic Surfaces Based on Water-Stimulated Hydrogen Bonding

Abstract: Reusable adhesives able to bond and debond to a surface as needed in response to stimuli are eagerly sought. Despite recent advances in catechol-derived adhesives, achieving strong and switchable adhesion persists as a challenge because easy catechol-to-quinone oxidation invariably reduces the adhesive catechol units which induce the formation of irreversible cross-linked networks. For this study, a supramolecular adhesive carrying a hydrophobic tetramethylcyclotetrasiloxane (TMCS) core surrounded by hydrophil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 41 publications
(75 reference statements)
0
8
0
Order By: Relevance
“…The curves of G ′ and G ″ will intersect, and the film transits from an elasticity-dominated solid-like state to a viscosity-dominated melt state. With the increase of HO–FDAM–OH amount, the intersection point temperature gradually increases and they are 54 °C for PUFD-0.5, 82 °C for PUFD-1, and 84 °C for PUFD-1.5, PUFD-1, and PUFD-1.5, which is related to the enhanced hydrogen-bonding interactions and the elevated rigidity of the chain segments . However, it needs to be noted that due to the lower molar mass and wider molar mass dispersity of PUFD-2, its low molar mass component indeed acts as a plasticizer and the intersection temperature of PUFD-2 shifts to a lower temperature of about 75 °C.…”
Section: Resultsmentioning
confidence: 97%
“…The curves of G ′ and G ″ will intersect, and the film transits from an elasticity-dominated solid-like state to a viscosity-dominated melt state. With the increase of HO–FDAM–OH amount, the intersection point temperature gradually increases and they are 54 °C for PUFD-0.5, 82 °C for PUFD-1, and 84 °C for PUFD-1.5, PUFD-1, and PUFD-1.5, which is related to the enhanced hydrogen-bonding interactions and the elevated rigidity of the chain segments . However, it needs to be noted that due to the lower molar mass and wider molar mass dispersity of PUFD-2, its low molar mass component indeed acts as a plasticizer and the intersection temperature of PUFD-2 shifts to a lower temperature of about 75 °C.…”
Section: Resultsmentioning
confidence: 97%
“…[9][10][11][12][13] The most attractive mechanism for developing DoD adhesives that are reversibly detachable on demand is incorporating a system of reversible bond breaking and forming into the material design. [3][4][5] Dynamic covalent bonds, which are distinguished by their reversibility and responsiveness to external stimuli such as heat, light, electricity, and pH, can control the degree of polymerization, crosslink density, and viscoelastic properties of polymeric materials. [14][15] Recently, stimulus-responsive dynamic covalent bonding has been shown to be applicable to adhesives in terms of controlling adhesiveness.…”
Section: Introductionmentioning
confidence: 99%
“…Over the past decade, debonding-on-demand (DoD) systems with a variety of bond strengths according to requirements have been developed in the medical, automotive, micro, and soft electronics fields. [1][2][3][4][5] These DoD adhesives are required to possess switchable adhesiveness, that is, they should be sufficiently strong to hold and bond adherends when in use, while decreasing in strength sufficiently to be peeled off from the adherends after use. For example, acrylic-and silicone-based adhesives are mainly used as peelable wound dressings in the biomedical field.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, dopamine has received much attention due to its high adhesion, good hydrophilicity, and bioactivity. Dopamine contains much catechol and amine groups, which can undergo autoxidative polymerization under weak alkaline conditions to form polydopamine (PDA) coatings and adsorb to various substrate surfaces through covalent- and noncovalent-bonding interactions. In addition, PDA coatings can be used as a secondary functionalization platform because the phenolic hydroxyl and amine groups in PDA coatings can be used for molecular modification and loading transition-metal ions. However, the high price of dopamine severely limits its development in the industrial field. Fortunately, it has been shown that the cross-linked network formed by the phenolic hydroxyl groups and autoxidative polymerization is the key to the outstanding adhesion of PDA. Wang et al used inexpensive catechol (CA)/polyamine (PA) to modify the aramid fibers and further bridged the silane coupling agent, which significantly improved the interfacial adhesion of the modified aramid fibers to the rubber matrix. Gu et al modified aramid fibers with catechol/polyamine (CPA), and the wet shear strength of the prepared aramid fiber-reinforced SPI-based adhesive was increased by 133.3%.…”
Section: Introductionmentioning
confidence: 99%